The need for dedicated advanced heart failure units to optimize heart failure care: impact of optimized advanced heart failure unit care on heart transplant outcome in high-risk patients - Kreußer, Michael; Tschierschke, Ramon; Beckendorf, Jan; Baxmann, Tobias; Frankenstein, Lutz; Dösch, Andreas; Schultz, Jobst-Hendrik; Giannitsis, Evangelos; Pleger, Sven Torsten; Ruhparwar, Arjang; Karck, Matthias; Katus, Hugo; et al. (ESC heart failure, 2018)
Aim With an increasing prevalence of heart failure (HF), more patients with advanced disease have to be treated in cardiology units by sophisticated medical and interventional strategies. We therefore developed a dedicated advanced heart failure unit (AHFU) to target the specific needs of the many patients with advanced HF. We here present our concept and its impact on outcome in high-risk high-urgency (HU) heart transplant candidates. Methods and results The eight-bed unit was established as an extension of the cardiologic intensive care and coronary care units in an intermediate care setting. Each bed was equipped with 24 h haemodynamic, respiratory, and arrhythmia monitoring. The unit is served 24/7 by five residents in cardiology, one staff cardiologist specializing in medical and interventional HF care, and 10 intensive care nurses. The cardiology team is supported by colleagues from cardiac surgery, sports medicine, psychosomatics, and the internal medicine departments. As an example of the intensified care on the AHFU, data from the cohorts of patients undergoing heart transplantation from HU status before (pre-AHFU 2008-11) and after establishment of the AHFU (AHFU 2012-15) were analysed. Interestingly, mortality on HU waiting list and post-heart transplant survival was comparable in both cohorts, despite significant increase in morbidity and co-morbidity as assessed by the Index for Mortality Prediction After Cardiac Transplantation model in the AHFU group. Conclusions Our AHFU provides a unique and novel setting for the integration of modern pharmacological, interventional, surgical, and supportive HF therapy embedded in an academic heart centre. This may be a major step forward in the care of critical patients with advanced HF.